Involvement of mitochondria in acetaminophen-induced apoptosis and hepatic injury: roles of cytochrome c, Bax, Bid, and caspases. - El-Hassan, H; Anwar, K; Macanas-Pirard, P; Crabtree, M; Chow, S; Johnson, V; Lee, P; Hinton, R; Price, S; Kass, G (2003)
The role of apoptosis in acetaminophen (AAP)-induced hepatic injury was investigated. Six hours after AAP administration to BALB/c mice, a significant loss of hepatic mitochondrial cytochrome c was observed that was similar in extent to the loss observed after in vivo activation of CD95 by antibody treatment. AAP-induced loss of mitochondrial cytochrome c coincided with the appearance in the cytosol of a fragment corresponding to truncated Bid (tBid). At the same time, tBid became detectable in the mitochondrial fraction, and concomitantly, Bax was found translocated to mitochondria. However, AAP failed to activate the execution caspases 3 and 7 as evidenced by a lack of procaspase processing and the absence of an increase in caspase-3-like activity. In contrast, the administration of the pan-inhibitor of caspases, benzyloxycarbonyl-Val-Ala-DL-Asp-fluoromethylketone (but not its analogue benzyloxycarbonyl-Phe-Ala-fluoromethylketone) prevented the development of liver injury by AAP and the appearance of apoptotic parenchymal cells. This correlated with the inhibition of the processing of Bid to tBid. The caspase inhibitor failed to prevent both the redistribution of Bax to the mitochondria and the loss of cytochrome c. In conclusion, apoptosis is an important causal event in the initiation of the hepatic injury inflicted by AAP. However, as suggested by the lack of activation of the main execution caspases, apoptosis is not properly executed and degenerates into necrosis.